2024
DOI: 10.1039/d3ey00193h
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in understanding the catalyst layer in anion exchange membrane electrolyzers – durability, utilization, and integration

Emily K. Volk,
Melissa E. Kreider,
Stephanie Kwon
et al.

Abstract: This review discusses recent insights in catalyst layer design strategies for anion exchange membrane water electrolyzers, including electrode design, catalyst/ionomer integration, operational variables, in situ diagnostics, and cell durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 195 publications
(479 reference statements)
0
4
0
Order By: Relevance
“…R charge represents the interfacial resistance between the electrode and the electrolyte. 61–63 In general, stronger adhesion between the membrane and the catalyst layers results in lower interfacial resistance, consequently reducing R charge .…”
Section: Resultsmentioning
confidence: 99%
“…R charge represents the interfacial resistance between the electrode and the electrolyte. 61–63 In general, stronger adhesion between the membrane and the catalyst layers results in lower interfacial resistance, consequently reducing R charge .…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive method is essential to optimize the durability and performance of AEMWE systems. [38][39][40][41] The impact of OH À and Cl À concentrations on the activity and stability of the OER and HER catalysts is of particular interest for direct seawater electrolysis. [42] As shown in Table 1 hydroxyl ions are formed during the HER, which increases the pH and negatively impacts the activity of the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…31,33 While AEMWE does not have the same limitations of catalyst cost, the properties of the catalyst, ionomer, and PTL are currently inferior to those of PEMWE. 34 First, the transition metal oxides typically used as alkaline OER catalysts have orders of magnitude lower electronic conductivity than IrO 2 , which can lead to large ohmic losses. 35 A study comparing OER catalysts in RDE and AEMWE found that catalyst performance in AEMWE was more strongly correlated to the conductivity of a catalyst than its intrinsic OER activity.…”
Section: Introductionmentioning
confidence: 99%
“…While AEMWE does not have the same limitations of catalyst cost, the properties of the catalyst, ionomer, and PTL are currently inferior to those of PEMWE . First, the transition metal oxides typically used as alkaline OER catalysts have orders of magnitude lower electronic conductivity than IrO 2 , which can lead to large ohmic losses .…”
Section: Introductionmentioning
confidence: 99%